Determining How Critical Zone Structure Constrains Hydrogeochemical Behavior of Watersheds: Learning From an Elevation Gradient in California's Sierra Nevada - Ackerer, Julien; Steefel, Carl; Liu, Fengjing; Bart, Ryan; Safeeq, Mohammad; O'Geen, Anthony; Hunsaker, Carolyn; Bales, Roger (Frontiers in Water, 2020)
Concentration-discharge (C-Q) relations can provide insight into the dynamic behavior of the Critical Zone (CZ), as C-Q relations integrate the spatial distribution and timing of watershed hydrogeochemical processes. This study blends geomorphologic analysis, C-Q relations and reactive-transport modeling using a rich dataset from an elevation gradient of eight watersheds in the Southern Sierra Nevada, California. We found that the CZ structure exerts a strong control on the C-Q relations, and on the hydrogeochemical behavior of headwater watersheds. Watersheds with thin regolith, a large stream network, and limited water storage have fast mean transit times along subsurface flow lines, and show limited seasonal variability in ionic concentrations in streamflow (i.e. chemostatic behavior). In contrast, watersheds with thicker regolith, a small stream network and more water storage have longer transit times along subsurface flow lines, and exhibit greater chemical variability (i.e. chemodynamic behavior). Independent estimates of mean transit times and water storage from other isotopic, hydrologic and geophysical studies were consistent with results from modeling C-Q relations. The stream chemistry and its variability were controlled by lateral flow within the regolith, and no mixing with deep groundwater was needed to explain the observed chemical variability. This study opens the possibility to estimate water-storage capacity and mean transit times, and thus drought resistance in watersheds, by using quantitative modeling of C-Q relations.